A simulative overview on fiber predictions models for discontinuous long fiber composites. Issue 1 (29th July 2019) - Kuhn, Christoph; Koerner, Enrico; Taeger, Olaf
Abstract: During the molding of fiber reinforced plastics, complex behavior of long fibers are observed which lead to significant changes in fiber orientation and fiber content distribution as compared to short fiber reinforced plastics. In earlier publications, a direct fiber simulation approach with a mechanistic model has been presented to display the complex fiber behavior inside simple geometries, which is mainly influenced by fiber interactions during flow. In this article, the prediction with the mechanistic model is evaluated in a complex geometry and compared to commercially available direct fiber simulation as well as traditional simulation tools. In this overview, the fiber parameters of fiber orientation and fiber content distribution are analyzed and compared to experimental data. Conclusively, it is shown that the predictions with a mechanistic model show the most accurate results regarding fiber orientation and fiber content distribution, with the downside of a significantly longer computational time.